Mammographic Breast Positioning Assessment via Deep Learning - Tanyel, Toygar; Denizoglu, Nurper; Seker, Mustafa Ege; Alis, Deniz; Cerekci, Esma; Karaarslan, Ercan; Aribal, Erkin; Oksuz, Ilkay (SPRINGER INTERNATIONAL PUBLISHING AG, 2025)
1st Deep Breast Workshop on Artificial Intelligence and Imaging for Diagnostic and Treatment Challenges in Breast Care-Deep-Breath, Marrakesh, MOROCCO, OCT 10, 2024
Keywords: Breast cancer; Mammography; Deep learning; Positioning assessment